2019
DOI: 10.1111/rda.13600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different intracellular cryoprotectants on the solid surface vitrification of red‐rumped agouti (Dasyprocta Leporina Lichtenstein, 1823) ovarian tissue

Abstract: In contributing to the conservation of wild rodents, the aim of this study was to evaluate the use of distinct cryoprotectants, separately or in combination, for solid surface vitrification (SSV) of red‐rumped agouti ovarian tissue. Ovarian cortex from nine females was recovered and fragmented. Fresh fragments (control) were used to analyse the pre‐antral follicle (PF) morphology using a histologic procedure, viability using the Trypan blue test, cell proliferation by counting the argyrophilic nucleolar organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Analysis of the results indicated that PROH was the best cryoprotectant agent of the three evaluated and thus was recommended. The use of DMSO and EG for solid-surface vitrification (SSV) was also proven effective in the preservation of ovarian tissue, with 3 M EG being the most effective [ 16 ].…”
Section: Agouti ( Dasyprocta Leporina )mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the results indicated that PROH was the best cryoprotectant agent of the three evaluated and thus was recommended. The use of DMSO and EG for solid-surface vitrification (SSV) was also proven effective in the preservation of ovarian tissue, with 3 M EG being the most effective [ 16 ].…”
Section: Agouti ( Dasyprocta Leporina )mentioning
confidence: 99%
“…Agoutis ( Dasyprocta spp.) are medium-sized rodents that weigh between 2–3.5 kg [ 13 , 14 , 15 , 16 , 17 ]. Studies defining the age of puberty in females are lacking, however, Guimarães et al [ 18 ] showed that, under the male effect, puberty in D. prymnolopha was attained at nine months.…”
Section: Introductionmentioning
confidence: 99%
“…From the 13 catalogued agouti species, only three remain presenting a stable population, including the Dasyprocta leporina , the red-rumped agouti, that inhabits Brazilian Caatinga ( Emmons and Reid, 2016 ). At this sense, various efforts related to ex situ conservation strategies, as the biobank formation ( Castelo et al, 2015 ; Praxedes et al, 2020 ; Rodrigues et al, 2021 ), have been conducted to help on the efforts to maintain the stability of free-living D. leporina populations and provide technologies for its captive sustainable breeding ( Lall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protocols to create BRB from ovarian and testicular tissues have been developed in different wild species ( Campos et al, 2019b , Praxedes et al, 2020 , Silva et al, 2021a , b , 2022 ). In general, the efficiency of BRB of preantral follicles (PAFs) enclosed in ovarian tissues or germ cells enclosed in testicular tissues depend on the technical conditions involved in the recovery, cryopreservation, in vivo or in vitro culture and characterization of these tissues, which are all species-specific ( Campos et al, 2019b , Silva et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%